Fault-tolerant prescribed performance control of active suspension based on approximation-free method. Issue 5 (4th May 2022) - Wu, Yang; Li, Boyuan; Du, Haiping; Zhang, Nong; Zhang, Bangji
ABSTRACT: This paper proposes a fault-tolerant controller for active suspension to improve the bounce and pitch performance of a half-car system. In order to guarantee both the transient and steady-state control objectives, the prescribed performance control (PPC) method is applied to regulate the convergence rate, overshoot and tracking error of the closed-loop (CL) system. The system parametric uncertainties including sprung mass, sprung pitch inertia, suspension stiffness and damping coefficient, and axle distances are considered. The dynamics of three types of frequently encountered actuator faults are elaborated. Unlike most of the existing studies that use the adaptive method or neural network (NN) to estimate the uncertain parameters, this paper proposes a novel approximation-free method to deal with the uncertainties. The stability of the CL system is rigorously proved, and the suspension performance is examined with respect to physical constraints. In the numerical simulation, two kinds of imperfect actuators with hybrid nonlinear characteristic are employed to verify the effectiveness of the proposed controller. Simulation results show that the proposed controller can effectively suppress the bounce and pitch motions for the sprung mass and is robust to system uncertainties and actuator faults.